Masses of ground-state mesons and baryons, including those with heavy quarks - Yin, Pei-Lin; Chen, Chen [UNESP]; Krein, Gastão [UNESP]; Roberts, Craig D.; Segovia, Jorge; Xu, Shu-Sheng (American Physical Society (APS), 2019)
Using a confining, symmetry-preserving regularization of a vector×vector contact interaction, we compute the spectra of ground-state pseudoscalar and vector (fg) mesons, scalar and axial-vector (fg) diquarks, and JP=1/2+,3/2+ (fgh) baryons, where f,g,h∈{u,d,s,c,b}. The diquark correlations are essentially dynamical and play a key role in formulating and solving the three-valence-quark baryon problems. The baryon spectrum obtained from this largely algebraic approach reproduces the 22 known experimental masses with an accuracy of 2.9(2.4)%. It also possesses the richness of states typical of constituent-quark models, predicting many heavy-quark baryons not yet observed. This study indicates that diquark correlations are an important component of all baryons; and owing to the dynamical character of the diquarks, it is typically the lightest allowed diquark correlation that defines the most important component of a baryon's Faddeev amplitude.